The National and University Library of Iceland 200th Anniversary - Ekaterina A. Barysheva; Екатерина Александровна Барышева (Bibliotekovedenie [Russian Journal of Library Science], 2019)
The National and University Library of Iceland (Landsbókasafn Íslands — Háskólabókasafn) celebrated its 200th anniversary in 2018. The purpose of the review is to acquaint Russian library specialists with the history of this institution and to show its role in the preservation and promotion of the national cultural heritage. The author considers the main stages of development of the National and University Library of Iceland (NULI): from the establishment of the Icelandic Provincial Library in Reykjavík in 1818 (in 1881 it was renamed to the National Library of Iceland) to its merger with the University Library in 1994. The main sources of the study are the articles of foreign, primarily Icelandic, researchers on the activities, holdings and electronic collections of NULI, published in the late 1990s — 2010s. The author notes the contribution of Jón Árnason (1819—1898), the famous Icelandic researcher-folklorist and the first national librarian, who headed the library for about 40 years, in the development of the institution’s structure and stocks. The paper characterizes the modern organizational and management structure of NULI, composition of collections (including the Manuscript Department and the Icelandic Department), the system of library and bibliographic services. The author emphasizes the role of the Árni Magnússon Institute for Icelandic Studies in Reykjavík as the main repository and centre for the study of Icelandic manuscripts. The institute conducts the intensive work on search for medieval Icelandic documents in the libraries and archives of other states and the digital reconstruction of scattered collections. The article reveals the work of NULI on opening of its holdings and creation of digital collections (“Collection of historical maps of Iceland”, “Digital library of medieval Icelandic manuscripts”, “Digital library of Icelandic Newspapers and magazines”, “Collection of old books of Iceland”, etc.). The author draws particular attention to the activities of the Consortium of Icelandic ...